Relationships between Sleep Problems and Psychiatric Comorbidities among China's Wenchuan Earthquake Survivors Remaining in Temporary Housing Camps - Jiang, Suo; Yan, Zheng; Jing, Pan; Li, Changjin; Zheng, Tiansheng; He, Jincai (Frontiers in Psychology, 2016)
Earthquake survivors are a diverse population. This study focused on a special group of earthquake survivors, who had still stayed in temporary housing camps for about two years after China’s Wenchuan Earthquake rather than those who moved back to rebuild their lives or immigrated to large cities to seek new lives. The research goals were to (1) assess their sleep problems as well as their PTSD, depression and anxiety and (2) examine the relationship between different dimensions of sleep quality and PTSD, depression, and anxiety among these survivors. 387 earthquake survivors who remained in temporary housing camps and had sleep problems were recruited 17 to 27 months after Wenchuan Earthquake. Four standardized instruments-The Pittsburgh Sleep Quality Index, PTSD Checklist-Civilian Version, Self-rating Depression Scale, Self-rating Anxiety Scale, and face-to-face one-on-one structured interviews were used to assess these survivors’ sleep quality, PTSD, depression and anxiety. It was found that (1) 83.20% of these survivors reported having sleep problems, and 79.33% of them considered insomnia as the most common sleep problem; (2) 12.14% suffered PTSD, 36.43% experienced depression, and 38.24% had anxiety; (3) sleep disturbance, sleep medication use, and subjective sleep quality were significantly related to PTSD; (4) habitual sleep efficiency, sleep disturbance, sleep medication use, and daytime dysfunction were significantly related to depression; and (5) sleep disturbance, sleep medication use, and daytime dysfunction were significantly related to anxiety. Clinic implications of the study are discussed.